DAMPAK PEMULIHAN JASA TERHADAP KEPUASAN PELANGGAN: SEBUAH PERBANDINGAN ANTARA PELANGGAN YANG KOMPLAIN DAN PELANGGAN YANG TIDAK KOMPLAIN (STUDIKASUS: SERVICE CENTER ESIA DIMARGONDA DEPOK) - Rusli Fauzan; Rizal Edy Halim (Universitas Trisakti, 2008)
Nowadays, the industry of telecommunication service provider in Indonesia is thriving. Telecommunication operators, both GSM-based and CDMA-based, compete for bigger share of the market. We can see that there are a lot of packages and added features offered. However, service failures still occur that requires providers to do service recoveries. Good service recovery after service failure occurrences is identified in the service industry as one of the key for customer loyalty.This research aims to determine the effect of dimensions of justice toward the customer satisfaction in the service recovery of Indonesian telecommunication provider, in this case ESIA, and compares the customer satisfaction of each customer by trust, word of mouth and customer loyalty between complaining and non-complaining customer.The result shows that customer complaint influenced by two variables from dimensions of justice through interactional justice and distributive justice. Besides that, result shows that service recovery satisfaction influences customer response after service recovery is completed, in form of trust, word of mouth and customer loyalty.Keywords: Seivice recovery, Customer satisfaction, Customer complaint